The dynamics of microbial communities in the host, water and sediment during the metamorphosis of Ruditapes philippinarum larvae - Yong Huang; Hongxia Wang; Jun Fang; Pin Huan; Baozhong Liu (Aquaculture, 2026)

Structure-Constrained Prior Ensembles for ES-MDA Post-Stack Acoustic Impedance Inversion - Zhi-fang Ran; Yin-quan Hao; Pin Zhang; Weiwei Gu; Guo-fa Li (Applied Geophysics, 2026)

Microbiological spectrum, clinical outcomes, and risk factors for bloodstream infections during immune checkpoint inhibitor therapy: a nested case-control study - Deng Pan; Huan Wang; Yu Fang; Jun Lu; Wendi Zhang; Pin Peng; Minghao Fang (Infectious Diseases, 2026)

Infrared thermal imaging as a non-invasive predictive tool for early detection of flap necrosis after breast cancer surgery: A prospective cohort study - Jiangnan Yao; Pin Fang; Haiyan Zhang; Ping Liu; Xiaoqiong Jiang; Pan Huang; Fuman Cai (Journal of Thermal Biology, 2026)

Pyrolysis behaviors of lump sub-bituminous coal. Part 2: Effect of particle size - Zong-Pin Fu; Le-Le Qiu; Yi-Bin Huang; Yun-Peng Zhao; Jian Zhou; Jing Liang; Jian Xiao; Fang-Jing Liu (Fuel, 2026)

One-pot remediation of binary organic-metal pollution: Efficient co-removal of BPA and Sb(III) by PMS-activated Fe-Mn@NC catalyst - Shuoshuo Mao; Jingjing Liu; Shanqi Liang; Lei Li; Pin Gao; Fang Li; Juan Zhou (Journal of Environmental Chemical Engineering, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Identification, occurrence, and toxicity prediction of alkylphenolic disinfection by-products in disinfected combined sewer overflows - Yayun Zhang; Pin Wang; Rong Xiao; Wenyuan Yang; Fang Yuan Jiang; Wen Hai Chu (Journal of Hazardous Materials, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Innovative municipal sludge dewatering: High efficiency and high-dryness through the synergistic effect of MoS2 piezoelectric catalysis and electro-dewatering - Binqi Rao; Yulin Li; Zhuo Zeng; Yin Duan; Yan Zhang; Fang Zhou; Weilun Ren; Pin Zhou; Xilong Lu; Quanfa Zhou; Peng Xu (Journal of Environmental Management, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

On-device charge engineering in 2D perovskite oxides for high performance photodetectors - Yong Zhang; Lin Wang; Xiujun Wang; Xiaohang Pan; Pin Zhao; Ye Liu; Qing Guo; Lixing Kang; Xiaosheng Fang (Chemical Engineering Journal, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Casein/butyrylated dextrin nanoparticles and chitosan stabilized bilayer emulsions as fat substitutes in sponge cakes - Han Tao; Xiao-Han Fang; Pin Chen; Bao-Qiu Yang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

Development and Usability Testing of a Decision Support App for Women Considering Breast Reconstruction Surgery - Pin-Jun Lin; Su-Ying Fang; Yao-Lung Kuo (Journal of Cancer Education, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

MicroRNA-143–5p modulates pulmonary artery smooth muscle cells functions in hypoxic pulmonary hypertension through targeting HIF-1α - Bi Tang; Ming-ming Tang; Qing-mei Xu; Jian-lu Guo; Ling Xuan; Jing zhou; Xiao-jing Wang; Heng Zhang; Pin-fang Kang (Journal of Biosciences, 2020)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

Difference in soil bacterial community composition depends on forest type rather than nitrogen and phosphorus additions in tropical montane rainforests - Pin Li; Congcong Shen; Lai Jiang; Zhaozhong Feng; Jingyun Fang (Biology and Fertility of Soils, 2019)

Therapeutic value of nerve growth factor in promoting neural stem cell survival and differentiation and protecting against neuronal hearing loss - Zhao Han; Cong-Pin Wang; Ning Cong; Yu-Yan Gu; Rui Ma; Fang-Lu Chi (Molecular and Cellular Biochemistry, 2017)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

The potential roles of bacterial communities in coral defence: A case study at Talang-talang reef - Felicity W. I. Kuek; Li-Fang Lim; Lin-Hui Ngu; Aazani Mujahid; Po-Teen Lim; Chui-Pin Leaw; Moritz Müller (Ocean Science Journal, 2015)

Global patterns of soil microbial nitrogen and phosphorus stoichiometry in forest ecosystems - Pin Li; Yuanhe Yang; Wenxuan Han; Jingyun Fang (Global Ecology and Biogeography, 2014)
Aim To investigate broad‐scale patterns of soil microbial nitrogen ( N ) and phosphorus ( P ) stoichiometry and their environmental drivers. Location Global forests. Methods By synthesizing 652 observations of soil microbial biomass N and P derived from the published literature, we investigated global patterns of soil microbial N , P and N : P ratios and their relationships with climate, soil and vegetation types. Results Microbial N and P concentrations varied widely among forest types, with relatively low N and P concentrations but high N : P ratios in tropical forests. The N and P concentrations increased and the N : P ratio decreased with increasing latitude (or decreasing temperature). The N:P ratio showed a similar pattern along the precipitation gradient to that along the temperature gradient, whereas microbial N and P displayed weak trends along the precipitation gradient. Edaphic variables also regulated the patterns of microbial N and P stoichiometry: microbial N and P concentrations increased with soil N and P concentrations as well as with soil pH . Mixed‐effects models revealed that edaphic factors explained the largest part of the variation in microbial N , P and the N : P ratio, suggesting their dominant role. Main conclusions Our findings highlight that there are broad‐scale patterns in microbial N , P and the N : P ratio along the gradients of latitude, temperature and precipitation, which are similar to those reported in plants and soils. The consistency of these patterns in plant–soil–microbe ecosystems supports the hypothesis that P is more often the major limiting element at low latitudes than at high latitudes.

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose - Xian-Fang Meng; Xiao-Lan Wang; Xiu-Juan Tian; Zhi-Hua Yang; Guang-Pin Chu; Jing Zhang; Man Li; Jing Shi; Chun Zhang (Molecular Neurobiology, 2014)

MicroRNA-124 (miR-124) Regulates Ku70 Expression and is Correlated with Neuronal Death Induced by Ischemia/Reperfusion - Fei Zhu; Jing-Li Liu; Jing-Pin Li; Fang Xiao; Zhao-Xia Zhang; Lei Zhang (Journal of Molecular Neuroscience, 2014)

Spatio-temporal changes in biomass carbon sinks in China’s forests from 1977 to 2008 - ZhaoDi Guo; HuiFeng Hu; Pin Li; NuYun Li; JingYun Fang (Science China Life Sciences, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Study on agricultural benefits by increasing capacity of water ponds: a case study at Taoyuan paddy fields - Wen-Tsun Fang; Chuan-Pin Chien; Shu-Chen Chen (Paddy and Water Environment, 2012)

Modeling irrigation return flow for the return flow reuse system in paddy fields - Chuan-Pin Chien; Wen-Tsun Fang (Paddy and Water Environment, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Protection against HIV-envelope-induced neuronal cell destruction by HIV attachment inhibitors - Sharon Zhang; Louis Alexander; Tao Wang; Michele Agler; Nannon Zhou; Hua Fang; John Kadow; Paul Clapham; Pin-Fang Lin (Archives of Virology, 2010)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Mapping and assessing spatial multiscale variations of birds associated with urban environments in metropolitan Taipei, Taiwan - Yun-Bin Lin; Yu-Pin Lin; Wei-Ta Fang (Environmental Monitoring and Assessment, 2008)